Quality diagnosis of graphic services and printing in the city of Ambato - Santamaría Aguirre, Jorge; Lara Saltos, Andrea; Pilamunga Poveda, Marcelo (mktDESCUBRE; Vol 1 No 16 (2020): Sixteenth Edition (July - December), 2020)
The graphic industry has its history as a provider of printing services, the processes for its production involve stages and the inclusion of designers for its execution.  The use of the ISO 12647 standard controls the printing parameters to achieve a replicable and quality result.  A diagnosis on the handling of quality criteria in the management of processes related to the design applied to a defined sample by means of case studies to important companies of the environment, allows us to understand the context and reality of the sector, showing its deficiencies.  The results obtained are weighted to establish the most representative criteria to establish SWOT strategies that establish actions based on strengths, weaknesses, threats and opportunities of the printing centers to improve the stages of graphic production and guarantee their quality.